Penerapan Sistem Akuntansi Berbasis Komunikasi Kepada Pengrajin Sarung Tenun di Desa Kampung Baru Kabupaten Nganjuk - Kumalasari, Resti; Arifin, Syamsul; Darim, Abu; Adhitya, Devangga Putra (CV. Ulil Albab Corp, 2025)
This study aims to describe the implementation of a communication-based accounting system for woven sarong artisans in Kampung Baru Village, Nganjuk Regency. The background of this research is based on the fact that the majority of artisans still conduct financial record-keeping in a simple manner, and many do not have a structured accounting system. This condition hinders the monitoring of cash flow, calculation of production costs, and determination of business profits. The research method used is qualitative descriptive, with data collection techniques through interviews, observation, and documentation. The informants consist of woven sarong artisans, village officials, and relevant parties who understand business activities in the area. Data analysis was carried out through stages of reduction, data presentation, and conclusion drawing. The results show that a simple communication approach adapted to daily life can improve artisans’ understanding of the importance of financial record-keeping. The implementation of a communication-based accounting system can be a first step in building an accountable record-keeping culture, although it still requires assistance and habituation. In addition, the use of digital recording applications has proven to potentially facilitate the accounting process, although adoption depends on the community’s level of digital literacy. This study concludes that a communication-based accounting system can be a transformative solution for woven sarong artisans to enhance transparency, accountability, and business sustainability. It is recommended that village governments and related institutions provide training and supporting facilities, while future research could examine the effectiveness of using digital accounting applications and add other variables relevant to the empowerment of micro businesses.